An Integration Mind And Body In Psychodermatology - Fernanda Silva Hoffmann; Hericka Zogbi; Patrícia Fleck; Marisa Campio Müller (Psicologia, 2005)
Nowadays there has been an increase in the studies which involve the integration between medical and psychological aspects, that is, between body and psyche subjects. In this way this article aims at revising the theoretical findings related to Psychodermatology, allowing a critical reflection concerning to the subject and its possible new directions. We know that Psychodermatology is a branch which aims at the study and treatment of dermatologic problems which are caused ad/or influence by psychological factors. The links which exist with the nervous system make the skin highly sensitive to emotions regardless of our conscience. Therefore the skin, many times, expresses our feelings even when we are not aware of them. So, the idea that remains is that when we talk about skin diseases we should consider the human being integrally. Social, biological and psychological aspects are constantly interacting.